Eye lens diameter and weight as an age indicator in two sparid fishes off Benghazi coasts, Libya - Al Hassan, L A J; El Toumy, F F; El Silini, O A; El Burasi, H (Indian Journal of Fisheries, 2011)
The eye lens diameter and weight in the sparid fishes, Boops boops and Diplodusannularis, were tested for their vahdity as age indicators. The results showedthat the eye lens diameter in B. boops could be used to differentiate fishes in their2"'' and 3"' years of life from those of the 1*" and 2"'' year classes. On the otherhand, in D. annularis, this technique succeeded to differentiate S"' and 2"^ yearclasses. Eye lens weight technique proved well to differentiate fishes in the 0and 1 year class of B. boops from the remaining age groups. On the other hand,it proves not a good criterion to differentiate among the fish age groups of D.annularis except for l'''^ and 3'''' year classes.